Pengaruh Testimoni, Promosi, dan Harga Terhadap Minat Beli TopUp Voucher Game Mobile Legend (Komunitas ESJV Game Mobile Legend di Lamongan) - Nanto Purnomo; Ghaza Muhammad Enna Al-Ghazali (Departement of Mathematics Education, 2024)
This study is to determine the effect of testimonials, promotions, and prices on buying interest with a quantitative approach. This research is quantitative research. The object of research is ESJV community members. Sampling using the slovin formula obtained the final result of 133 respondents. The sampling method is simple random sampling. The method used is to use a questionnaire test distributed via online media. Based on the results of the validity and reliability tests, the testimonial (X), promotion (X), price (X) and purchase intention (Y) variables can be concluded to be valid and reliable based on the calculation test criteria. Statistical testing was carried out using SPSS Version 26. From the results of the testimonial hypothesis test, it has a positive and significant effect on purchase intention. Promotion has a positive and significant effect on buying interest. And, price has a positive and significant effect on buying interest.